PENGEMBANGAN MEDIA PEMBELAJARAN ELEKTRONIK MENGGUNAKAN EDMODO DALAM MENINGKATKAN PEMAHAMAN KONSEP PELAJARAN EKONOMI - Zainal, Zainal; Asriati, Nuraini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted at SMAN 1 Sambas, the aim of this research were to develop electronic learning media using edmodo; analyze the feasibility of learning media and to analyze the effectiveness of learning media using edmodo in improving students' concept comprehension. The research method was Research and Development (R&D) using ADDIE development models, namely: "Analysis, Design, Development, Implementation and Evaluation". The techniques of data collection were indirect communication techniques, measurement and documentation. The techniques of data analysis were qualitative data and quantitative data analysis. The results of the study: (1) The development of electronic learning media using edmodo through 5 stages, namely: analysis, design, development, implementation and evaluation (2) The results of the study showed that the feasibility of electronic learning media using edmodo from the assessment of material expert obtained a score 45 which was categorized as excellent; the assessment of media expert obtained a score 55 which was categorized as excellent and the assessment of the economics teacher obtained a score 43 which was categorized as very good. (3) Electronic learning media using edmodo was effective in improving students' concept comprehension, where the students’ concept comprehension of mean score was 6.4 in the pre-test before the implementation of developed learning media, then it increased to 7.2 in the post-test after the implementation of the developed media. Keywords: Electronic Learning, Edmodo, Understanding Concepts